Diet change of hadal amphipods revealed by fatty acid profile: A close relationship with surface ocean. (November 2018) - Shi, Linlin; Xiao, Wenjie; Liu, Zhiguo; Pan, Binbin; Xu, Yunping
Abstract: The diet of hadal organisms remains elusive because of the difficulty in sampling and monitoring at the great water depths (6–11 km). Here we analyzed fatty acids of the amphipods collected from three Pacific trenches, namely New Britain Trench (NBT; 8.2–8.9 km), Mariana Trench (MT; 11 km) and Massau Trench (MS; 6.9 km). A total of 35 fatty acids including saturated, monounsaturated and polyunsaturated compounds were identified. The principal component analysis (PCA) divides major fatty acids into three groups indicative of carrion (C20:4ω6, C22:5ω6, C22:6ω3, C16:1ω7, and C18:1ω9 ), algae (C18:2ω6 and C20:5ω3 ) and bacteria (C15:0, isoC15:0, isoC17:0, anteisoC17:0 and C17:0 ), respectively. The predominance of C18:1ω9, high C18:1ω9 /C18:1ω7 and high δ 15 N values suggest that hadal amphipods are necrophagous. The inter-trench comparisons based on C18:1ω9 /C18:1ω7, C22:6ω3 /C20:5ω3, ∑polyunsaturated/∑saturated fatty acids, ∑branched fatty acids and PCA show that the amphipods in the NBT are more dependent on high-quality organic matter (i.e., carrion), whereas those in the MT and MS utilize detritus and bacterial organic matter as supplementary food. This inter-trench difference has been attributed to a bottom-up effect of food availability that the NBT has higher net primary productivity (NPP) and a strong terrestrial influence, whereas the MT and MS have lower NPP and insignificant terrestrial influences. Our study demonstrates that the diet of hadal animals is closely related to surface ocean biogeochemical property. Highlights: Fatty acids of amphipods were analyzed for three trenches (6.9–11 km deep). Amphipods in moderate productive trench are primarily necrophagous. Amphipods in oligotrophic trenches consume detritus and bacterial organic matter. Inter-trench diet changes are related to surface ocean biogeochemical property.